Effects of different biomass substrates on the adsorption of antibiotics and beta-blockers - Aishwaryavathy, Muthu Kumar (2025)
Micropollutants are one of the growing environmental concerns because they cause many adverse effects on humans and the environment; one of the micropollutants present in the environment is pharmaceutical compounds. In this study, the adsorption of two types of pharmaceutical compounds, chloramphenicol and atenolol, onto substrates derived from agricultural waste, namely rice straw, sugarcane bagasse and corn cob, was studied. Zeolite was chosen as a control. The stock solution for the compounds was prepared at three different concentrations, and the adsorption test and characterization were conducted. The removal efficiency of the micropollutant was determined using HPLC, where all three biochar substrates successfully removed the chloramphenicol and atenolol from the spiked solution. However, the zeolite was not able to completely remove chloramphenicol. Then, for characterization, SEM, FTIR and BET were conducted. Based on the characterization, the sugarcane bagasse was identified as the best substrate for chloramphenicol and atenolol, this is because the sugarcane bagasse has the highest surface area compared to other substrates which is 556.60m2/g. Additionally, the sugarcane bagasse also has important functional groups that is necessary for the adsorption of the polar compound such as the carbonyl group. However, the other substrate also shows potential in adsorbing other types of micropollutants. The study mainly highlights the production of low-cost substrates that can remove the micropollutant completely from wastewater as well as the agricultural waste used sustainably.